PENGEMBANGAN BATAKO SISTEM INTERLOCKING UNTUK BANGUNAN TAHAN GEMPA - Diarto Trisnoyuwono; Marsinta Simamora; Priska Gardeni Nahak (JUTEKS : Jurnal Teknik Sipil, 2017)
Earthquakes as a natural phenomenon have caused many casualties and property.for the examples human casualties from the Aceh earthquake on December 26th, 2006 more than 180 thousand people, the Nias earthquake on March 15th, 2005 have more than 3000 of victims andlast the Yogyakarta earthquake on 27th May 2006 over 5700 victims. Based on observations most of the human victims caused by falling by the collapsed building. One of the elements of the building that is easy to fail when an earthquake strike is part of the wall.The walls are composed of clay bricks or concrete bricks only able to withstand axial force but weak in resisting lateral force perpendicular to the plane. Innovation model of brick to overcome the problem is batako interlocking system. Batako hooks (Interlock block) is a wall building material that has a hook to lock movement due to lateral force. Interlock block is the development of the brick by adding lips on certain sides as a lock. The developed brick model with a dimensions length of 30 cm, height of 15 cm and thickness of 10 cm, which is equipped with bulge / lips on all four sides. The portion of the mixture used is 1 cement: 5 sand. The molded brick was applied to a wall-mounted pairs product with a length of 1.5 m and a height of 1 m. Based on the calculation of material requirement from brick wall, it is known that the specific material for inserting an interlocking brick is 25% less than conventional batako pairs, besides the time required to obtain a neat pair of interlocking bricks is 7.5 minutes faster when compared with Installation of conventional brick.